Design and Performance Assessment of the AMI Infrastructure for the Universidad de Nariño’s Microgrid - Cervelión Bastidas, Álvaro José; Agredo Méndez, Guefry L.; Revelo Fuelagán, Javier (Ingeniería Solidaria, 2018)
Introduction: This article presents the design and performance assessment of the Advanced Metering Infrastructure ( AMI ) for a microgrid. This infrastructure enables the collection of consumer measurement data in a management center, essential to the construction of a microgrid. Aim:To design the communications network and select the equipment and management system for the AMI in the Universidad de Nariño’s microgrid. Methods: Literature review of the aspects to be considered in AMI design such as communication topologies, technologies and protocols, in addition to the metrics to assess AMI performance. Results:The AMI design is presented including measurement equipment, communications network and management center. Once the AMI was implemented, its performance was assessed according to the parameters of latency, bandwidth, throughput and packet loss. Conclusion:The results suggest that the flow in the microgrid. AMI meets the quality of service parameters, ensuring an optimal data Originality: While several initiatives have focused on the design of solutions based on microgrids and AMI s and on the study of their impacts, the implementation of these grids is still limited in Colombia. Limitations: For assessing the performance of the communications network, this study has considered the performance of communication channels, excluding the performance of various protocols used such as MODbus/TCP and DNP3/TCP .